Analisis Tourist Experience Terhadap Revisit Intention pada Objek Wisata Air Panas Se Kabupaten Garut - Rahyuniati Setiawan; Deri Alan Kurniawan (Entrepreneurship Faculty, Universitas Garut, 2019)
Tourist satisfaction is formed because of the experience felt by consumers after using the proposed products and services, giving rise to good value. The reputation of the region as a tourist destination must increase growth of the purpose of return visits for tourists is important for tourism managers so that marketing strategies are on target and effective. The diversity of tourist objects and and abundant natural tourist attractions such as cultural arts, historical tourism, shopping tourism and native crafts of the region have great importance to provide the best tourist experience for tourists so that it can be seen in the intention to re-visit. Tours on the experience for tourists or tourists. The research objectives of the analysis of tourist experiences on the intention to revisit hot air baths in Garut, consist of : (1) to obtain findings about the experience of tourists in hot air baths in Garut (2) to look for findings on the purpose of a return visit in hot air bathing attractions in Garut (3) to get a visit experience related to the intention to re-visit hot spring bathing attractions in Garut. While the research design that will be used is a systematic random sample and the type of sample used is a mobile population. By determining the respondent, determine the place as a check point, determine the time, and then ask for approval to be given a questionnaire. Questionnaires were measured using a Likert scale (ranking summary) each scale had 7 categories.